2021
DOI: 10.1182/bloodadvances.2021004735
|View full text |Cite
|
Sign up to set email alerts
|

Association of race and ethnicity with clinical phenotype, genetics, and survival in pediatric acute myeloid leukemia

Abstract: Black and Hispanic children with acute myeloid leukemia (AML) have worse outcomes compared to White children. AML is a heterogeneous disease with numerous genetic subtypes in which these disparities have not been specifically investigated. In this study, we used the Therapeutically Applicable Research to Generate Effective Treatments (TARGET) database to examine the association of race-ethnicity with leukemia cytogenetics, clinical features, and survival outcomes within major cytogenetic subgroups of pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 30 publications
(75 reference statements)
3
13
3
Order By: Relevance
“…Importantly, fewer statistically significant differences in presenting laboratory results were detected between Hispanic and non-Hispanic White patients. 9 In contrast to our findings, in a previous study a difference in median WBC was not found between Black and White children. 10 The lack of difference in that study may be due to selection bias caused by using trial-collected biospecimens, which favors children with lower acuity at presentation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Importantly, fewer statistically significant differences in presenting laboratory results were detected between Hispanic and non-Hispanic White patients. 9 In contrast to our findings, in a previous study a difference in median WBC was not found between Black and White children. 10 The lack of difference in that study may be due to selection bias caused by using trial-collected biospecimens, which favors children with lower acuity at presentation.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies suggest monocytic AML subtypes (including those with KMT2A rearrangements) present more frequently with elevated WBC count 8 . While KMT2A ‐rearranged AML is not broadly associated with Black race, the specific KMT2A ‐rearrangement t(6;11)(q27;q23) that carries a poor prognosis is more common among Black children 9 . In contrast to our findings, in a previous study a difference in median WBC was not found between Black and White children 10 .…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, a high frequency of t (8;21) in Black patients with AML has also recently been reported in pediatric AML, with 21.3% of Black vs 10.9% of non-Hispanic White patients harboring the t(8;21) translocation. 22 We observed differences in the frequencies of AML-associated mutations, with Black AYA patients harboring more often mutations in the ASXL1 [23][24][25] and BCOR 26-28 genes, which have been reported to confer worse outcomes, and carrying less frequently prognostically favorable NPM1 mutations 26,29 and biallelic mutations in the CEBPA gene. 26,30,31 Although the lower frequency of those 2 favorable risk markers we report herein may be considered as possible contributors to the inferior treatment outcome of Black AYA patients as compared with the outcome of White AYA patients, the previous notion of poor survival specifically of NPM1mutated/FLT3-ITD low/no younger Black patients with AML may instead raise the possibility of differences in the disease biology of favorable risk AML between Black and White patients with AML.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, this increased frequency seems to be especially pronounced in adolescent and young adult (AYA, aged 18–39 years) AML patients, in whom CBF-AML accounts for 37% of Black AML patients, compared to 22% of White patients in the same age group: in young Black patients t(8;21) accounted for 59% of CBF-AMLs, compared to 46% in White patients [36 ▪ ]. This predominance of t(8;21) was also seen in pediatric Black AML patients, in whom t(8;21) was twice as frequent compared to non-Hispanic Whites [37]. In contrast, 40% of young White AML patients present with cytogenetically normal karyotype at diagnosis, whereas only 19% of Black AYA AML patients have normal chromosomes.…”
Section: Introductionmentioning
confidence: 79%